The knowledge and power in Chinese education - Guo Zhou (Cogent Arts & Humanities)
The article explores the relationship between knowledge and power in the field of education in China. The article adopts the research method of documentary analysis to discourse analyse the classical literature in Chinese history. The article selects the Zhou Dynasty, the Han Dynasty, the Tang Dynasty, and the Song Dynasty as representatives of ancient China and the period of the Cultural Revolution as representatives of modern China. The goal of the article is to propose a structurally similar research perspective on Chinese education that can account for the co-temporal states between different periods in time. By initially applying this perspective to the study of Chinese education, its structure of knowledge and power shows a pattern of subordination of education to politics, which is internalised by the educated individuals through discipline in educational activities.